Compreensões de professores de matemática sobre a presença da álgebra no ensino fundamental II - Silva, Lais Cristina Pereira da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The studies of Algebra take an important role in the Brazilian school curriculum and they aim at enabling the student to develop and validate their abstraction and generalization skills. However, in the school scope, Algebra is a part of the Mathematics in which the learning process presents a variety of difficulties. Research and classroom experiments have shown that, even though students relate Math to symbols, many of them can't use such symbols as an auxiliary language to contribute with the mathematical thinking. They can't understand the procedures that make up the transformation in the algebraic expressions, that's why those students aren't able to develop or practice their capacity of abstraction and generalization. This end of course paper presents a research built up with teachers from a private school in the city of São José dos Campos - SP, about the Algebraic Thinking in Ensino Fundamental II - 6th to 9th years, in order to answer the guiding question: How do Mathematics teachers in Ensino Fundamental II understand Algebra? This is a qualitative research, developed according to a phenomenological approach. The intention of the research was to investigate how teachers understand, approach and use the techniques and procedures of the Algebraic Thinking with their students

O estudo da Álgebra constitui um espaço bastante significativo no currículo escolar brasileiro e tem por objetivo possibilitar que o aluno desenvolva e exercite sua capacidade de abstração e generalização. Contudo, no âmbito da prática escolar, a Álgebra constitui um campo da matemática no qual o processo de ensino e aprendizagem é permeado por muitas dificuldades. Experiências de pesquisa e de sala de aula têm mostrado que, embora os alunos associem a Matemática aos símbolos, muitos deles não conseguem utilizá-los como uma linguagem auxiliar para o raciocínio matemático, não compreendem os procedimentos que compõem as transformações de expressões algébricas e, diante disso, não desenvolvem e/ou exercem a sua capacidade de abstração e generalização. Neste Trabalho de Conclusão de Curso apresenta-se uma pesquisa desenvolvida com professores de uma escola da rede particular da cidade de São José dos Campos sobre o Pensamento Algébrico no Ensino Fundamental II - 6º ao 9º ano, com intuito de responder à pergunta norteadora: Como a Álgebra é compreendida por professores de Matemática do Ensino Fundamental II. Trata-se de uma pesquisa qualitativa, desenvolvida segundo uma abordagem fenomenológica. O intuito da pesquisa foi investigar como os professores entendem, abordam e utilizam as técnicas e procedimentos do Pensamento Algébrico com seus alunos
Mathematics teachers' comprehension on the presence of algebra in elementary school II
Keywords: Matemática - Estudo e ensino; Fenomenologia; Álgebra; Mathematics Study and teaching